2016
DOI: 10.1177/0883073816650036
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Headache and Cephalic Allodynia Attributed to Head Trauma in Children and Adolescents

Abstract: The aim of the study was to investigate clinical features of headache associated with minor versus moderate to severe traumatic brain injury and of posttraumatic versus primary headache in children and adolescents. Study group included 74 patients after mild (n = 60) or moderate to severe (n = 14) traumatic brain injury identified by retrospective review of the computerized files of a tertiary pediatric headache clinic. Forty patients (54%) had migraine-like headache, 23 (31.1%) tension-like headache, and 11 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…In particular, allodynia, pain in response to non-painful stimuli, is often measured in animal models. CA is common during a migraine attack (4042) and is also reported in over 50% of patients with post-traumatic headache (43,44). When sensory thresholds were tested in human subjects, 53% of patients with PTH displayed cephalic allodynia compared to only 20% of TBI patients who did not have PTH and 0% of control subjects (44).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, allodynia, pain in response to non-painful stimuli, is often measured in animal models. CA is common during a migraine attack (4042) and is also reported in over 50% of patients with post-traumatic headache (43,44). When sensory thresholds were tested in human subjects, 53% of patients with PTH displayed cephalic allodynia compared to only 20% of TBI patients who did not have PTH and 0% of control subjects (44).…”
Section: Discussionmentioning
confidence: 99%
“…Trauma causing muscle strain, vertebral misalignment, or ligamentous injuries may compress, irritate, or activate the occipital or trigeminal nerves, resulting in neuralgic pain in the distribution of the nerve and/or activation of central pain systems involved in headache 17 . In a study of children with PTH, a high rate of cutaneous allodynia was observed in those with PTH (53.8%), leading to the hypothesis that central sensitization might be a shared pathophysiological mechanism with migraine 18 . A recent review has nicely summarized different theories regarding the emergence and persistence of post‐traumatic headache 19 …”
Section: Pathophysiology Of Concussion and Post‐traumatic Headachementioning
confidence: 99%
“…These include symptom expectation, adjustment disorder, poor coping mechanisms, post‐traumatic stress disorders, anxiety, depression, sleep disorders, and other psychosocial stressors 9,20 . Medication overuse headache (MOH) may also alter the pathophysiology of PPTH and complicate recovery 18 …”
Section: Pathophysiology Of Concussion and Post‐traumatic Headachementioning
confidence: 99%
“…As animals cannot verbally indicate pain, in vivo models have focused on pain-related behavioural phenotypes considered indicative of headache. Cranial hypersensitivity, measured by Von Frey filaments, is one of the read-outs used to study cephalic cutaneous allodynia, which is present in both migraine [46] and post-traumatic headache [47] and reflects sensitization of the trigeminal system [48]. Using the same methodology, also peripheral (hind paw) hypersensitivity, which represents a marker of extra-cephalic allodynia, reflecting central sensitization at a level higher than the trigeminal system, may be assessed.…”
Section: Basic Science Preclinical Modelsmentioning
confidence: 99%